Hubungan Pengetahuan dan Citra Tubuh (Body Image) dengan Perilaku Personal Hygiene Siswa di SD Muhammadiyah Karangturi Banguntapan Bantul - Nadila; Susyana Candra Santi Dewi (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: An increase in health status can be achieved through personal hygiene, namely personal hygiene and health which includes skin hygiene, hair hygiene, nail hygiene, dental and oral hygiene, and clothing hygiene which aims to prevent disease in oneself and others. It is known that some students at elementary school Muhammadiyah Karangturi do not understand personal hygiene because of a lack of knowledge, body image, and personal hygiene behavior. Purpose: This study aims to determine the correlation between knowledge and body image with personal hygiene behavior of students at elementary school Muhammadiyah Karangturi Banguntapan Bantul Yogyakarta in 2022. Method: This study used a quantitative method with a cross-sectional research design. The population is 53 students and the sampling technique in this study is total sampling, which is a sample of 53 students. Data analysis using univariate and bivariate analysis. Based on the Chi Square test, it is known that there is a correlation between knowledge and personal hygiene behavior of students at elementary school Muhammadiyah Karangturi Banguntapan Bantul Yogyakarta, namely the value ? = 0.005 <? = 0.05 and there is a relationship between body image and personal hygiene behavior of students at elementary school Muhammadiyah Karangturi Banguntapan Bantul Yogyakarta, namely the value ? = 0.002 <? = 0.05. Conclusion: There is correlation between knowledge and personal hygiene behavior of students at elementary school Muhammadiyah Karangturi Banguntapan Bantul Yogyakarta and there is relationship between body image and personal hygiene behavior of students at elementary school Muhammadiyah Karangturi Banguntapan Bantul Yogyakarta.